Brain volume reduction predicts weight development in adolescent patients with anorexia nervosa. (September 2015) - Seitz, Jochen; Walter, Martin; Mainz, Verena; Herpertz-Dahlmann, Beate; Konrad, Kerstin; von Polier, Georg
Abstract: Background: Acute anorexia nervosa (AN) is associated with marked brain volume loss potentially leading to neuropsychological deficits. However, the mechanisms leading to this brain volume loss and its influencing factors are poorly understood and the clinical relevance of these brain alterations for the outcome of these AN-patients is yet unknown. Methods: Brain volumes of 56 female adolescent AN inpatients and 50 healthy controls (HCs) were measured using MRI scans. Multiple linear regression analyses were used to determine the impact of body weight at admission, prior weight loss, age of onset and illness duration on volume loss at admission and to analyse the association of brain volume reduction with body weight at a 1-year follow-up (N = 25). Results: Cortical and subcortical grey matter (GM) and cortical white matter (WM) but not cerebellar GM or WM were associated with low weight at admission. Amount of weight loss, age of onset and illness duration did not independently correlate with any volume changes. Prediction of age-adjusted standardized body mass index (BMI-SDS) at 1-year follow-up could be significantly improved from 34% of variance explained by age and BMI-SDS at admission to 47.5–53% after adding cortical WM, cerebellar GM or WM at time of admission. Conclusion: Whereas cortical GM changes appear to be an unspecific reflection of current body weight ("state marker"), cortical WM and cerebellar volume losses seem to indicate a longer-term risk (trait or "scar" of the illness), which appear to be important for the prediction of weight rehabilitation and long-term outcome. Highlights: MRI-brain scans of 56 adolescent anorexia nervosa patients were acquired at admission. BMI at admission was correlated with cerebral grey matter volumes. White matter and cerebellar volumes predicted weight at 1 year follow-up. Cerebral grey matter seems to reflect the current cachexic weight (state marker). White matter and cerebellum could indicate longer-term risk (trait or illness "scar").